ANALISIS MAKNA KONOTATIF DALAM DAKWAH USTAZ HANAN ATTAKI (KAJIAN SEMANTIK) - Faridhatun Nikmah (Jurnal Bahasa Lingua Scientia, 2019)
This study aims to analyze the meaning of Ustaz Hanan Attaki›s da›wah in semantic studies. This research uses descriptive qualitative method which means the results of the research are not in the form of numbers but rather the results of the description of words. The data source is in the form of Ustaz Hanan Attaki lecture document. In this study the data collected was in the form of a video lecture by Ustaz Hanan Attaki. The technique used in this study was the technique of referring and recording data through transcripts of writing from the results of listening and observing video lecture shows. The results of the study show that there are (a) seven words which include high connotation, such as shade, fragrant, kara, theory, hobbies, perfume; and (b) five words which include the form of friendly connotation meaning, such as the word chasing, understanding, giving, girl, and mature.